Bosonic Spectral Function and the Electron-Phonon Interaction in HTSC Cuprates - E. G. Maksimov; M. L. Kulić; O. V. Dolgov (Advances in Condensed Matter Physics)
In this paper we discuss experimental evidence related to the structure and origin of the bosonic spectral function 𝛼2𝐹(𝜔) in high-temperature superconducting (HTSC) cuprates at and near optimal doping. Global properties of 𝛼2𝐹(𝜔), such as number and positions of peaks, are extracted by combining optics, neutron scattering, ARPES and tunnelling measurements. These methods give evidence for strong electron-phonon interaction (EPI) with 1<𝜆𝑒𝑝≲3.5 in cuprates near optimal doping. We clarify how these results are in favor of the modified Migdal-Eliashberg (ME) theory for HTSC cuprates near optimal doping. In Section 2 we discuss theoretical ingredients—such as strong EPI, strong correlations—which are necessary to explain the mechanism of d-wave pairing in optimally doped cuprates. These comprise the ME theory for EPI in strongly correlated systems which give rise to the forward scattering peak. The latter is supported by the long-range part of EPI due to the weakly screened Madelung interaction in the ionic-metallic structure of layered HTSC cuprates. In this approach EPI is responsible for the strength of pairing while the residual Coulomb interaction and spin fluctuations trigger the d-wave pairing.